(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
The article presents an analysis of modern trends and innovative approaches in the field of digital marketing, which is becoming increasingly important for businesses. It discusses key factors that attract the attention of companies of all sizes and industries to electronic marketing. The analysis examines three main reasons why digital marketing is becoming the preferred choice for companies: the shift of consumers to digital channels, the possibility of targeting and collecting customer data, as well as personalized offerings based on "big data" analysis. Furthermore, innovative technologies actively used in digital marketing are discussed. Specifically, the application of artificial intelligence, improving user experience, using short educational videos and metaverses, as well as the evolution of influencer marketing and other aspects are explored. Special attention is also paid to the application of innovations to enhance the competitiveness of enterprises, with an example of successful implementation in the beer market. In conclusion, the prospects for the development of digital marketing are discussed, including simplifying the processes of collecting and exchanging information about sales and customers, improving the quality of after-sales service, and new opportunities for marketing in social networks based on the Internet of Things concept.